2015
DOI: 10.1371/journal.pone.0143551
|View full text |Cite
|
Sign up to set email alerts
|

Use of a High-Density Protein Microarray to Identify Autoantibodies in Subjects with Type 2 Diabetes Mellitus and an HLA Background Associated with Reduced Insulin Secretion

Abstract: New biomarkers for type 2 diabetes mellitus (T2DM) may aid diagnosis, drug development or clinical treatment. Evidence is increasing for the adaptive immune system’s role in T2DM and suggests the presence of unidentified autoantibodies. While high-density protein microarrays have emerged as a useful technology to identify possible novel autoantigens in autoimmune diseases, its application in T2DM has lagged. In Pima Indians, the HLA haplotype (HLA-DRB1*02) is protective against T2DM and, when studied when they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…The reactivity of plasma samples to 14 target antigens ( were selected since they were significantly associated with participants with T2DM who lacked the protective HLA haplotype based on our prior study, 24 and the remaining 3 target proteins (LXR-alpha, interleukin 1 beta [IL1B], and IAPP) were marginally associated in the pilot study but were known to be biologically relevant to obesity and T2DM based on the literature. [27][28][29] Test plasma was previously stored at −70°C.…”
Section: Measurement Of Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The reactivity of plasma samples to 14 target antigens ( were selected since they were significantly associated with participants with T2DM who lacked the protective HLA haplotype based on our prior study, 24 and the remaining 3 target proteins (LXR-alpha, interleukin 1 beta [IL1B], and IAPP) were marginally associated in the pilot study but were known to be biologically relevant to obesity and T2DM based on the literature. [27][28][29] Test plasma was previously stored at −70°C.…”
Section: Measurement Of Antibodiesmentioning
confidence: 99%
“…24 On the basis of specified statistical criteria or possible role in underlying biology of type diabetes, we then tested 70 of these proteins in a second confirmatory study in a moderately larger group (n = 90) identifying 14 as promising biomarkers. 24 However, in both initial exploratory studies, to maximize the potential difference between groups, we selected individuals with T2DM and without the protective SNP that tags the HLA-DRB1*16:02 haplotype for comparison with those with normal glucose regulation (NGR) and the presence of the protective haplotype. 24 Thus, prior studies were limited by small sample sizes and by the fact that it could not ascertained whether the identified autoantibodies were associated with T2DM, the protective SNP, or a combination.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ubiquitin‐proteasome system was reported to have a role in type 2 diabetes. UBE2M antibody had a higher signal in type 2 diabetes patients’ plasma with the lower insulin‐secretion human leukocyte antigen background. We observed that UBE2M was increased in two hepatic insulin resistance models, indicating that UBE2M possibly plays a key role in type 2 diabetes hepatic insulin resistance.…”
Section: Discussionmentioning
confidence: 61%
“…Clinically, being acquainted with HLA distribution is a sine qua non for bone marrow donating centers [16], [17], forensic medicine [18], studies of HLA related disease such as type 2 diabetes [19], [20], [21] or multiple sclerosis [22], designing peptide vaccine and monoclonal antibodies against tumors [23], [24], infectious agents [25], [26], [27] and autoimmune disease [20], [28], as well as infertility treatment and assisted reproductive technologies [29], [30], [31].…”
Section: Introductionmentioning
confidence: 99%